Hubungan Fungsi Keluarga, Tugas dan Struktur Keluarga dengan Perencanaan Pernikahan Remaja Putri Di Daerah Rural - maurida, nurul; Basri, Achmad Ali; Silvanasari, Irwina Angelia; Vitaliati, Trisna (Jurnal Kesehatan, 2025)
Marriage planning for women adolescent is one of the things that concern in maintaining reproductive health. One indicator of good marriage  planning is marriage at a mature age. The phenomenon that occurs is the rise of early marriage among women adolescent in rural areas. The family has a role in decision making in marriage  planning of women adolescent. The aim of this research is to analyze the relationship between family function, family task and family structure with marriage planning among women adolescent in rural areas. The research design is quantitative research with a cross sectional approach. The research sample was 100 women adolescent with a sampling technique using quota sampling. The inclusion criteria for the study were women adolescent in rural areas aged 13-18 years and the exclusion criteria were women adolescent with psychological disorders. The independent variables in this research were family function, family task  and family structure. The dependent variable of the research was marriage planning. The research instrument was developed from the concept of family nursing and the concept of normal age marriage and has gone through validity and reliability tests so that it was declared valid and reliable. Research data was analyzed using person chisquare. The results showed that the majority of respondents had good family function (75%), good family task (68%) and good family structure (75%). Most respondents have been marriage planning for > 18 years (81%). The results of the person chisquare analysis show that there was a relationship between family function and marriage planning (ρ = 0.001<0.05), there was a relationship between family task and marriage planning (ρ = 0.000<0.05) and there was  a relationship between family structure and marriage planning (ρ 0.001 <0.05). Increasing family knowledge is needed to form a family that is able to carry out the functions, task and structure of the family so that they can make good marriage planning decisions for women adolescent in rural areas.